The Moleschott Figures - O'Hara-May, Jane (Petits Propos Culinaires, 2024)
We are all familiar with the idea that the nutritional needs of human beings can be quantified. Figures for ’recommended daily intakes’ of the various nutrients are published by international and national authorities and often appear on the labels of packaged foods. When did all this begin? In this essay Dr Jane O’Hara-May, author of An Elizabethan Dyetary of Health, draws attention to the pioneer work in this field of Jacob Moleschott and to a paradox: the figures he worked out were frequently quoted over a period of seventy years and more, yet hardly anyone grasped the significance of his method of calculation.